Implementation of Bandung City Regional Regulation Number 5 of 2021 on the Prevention and Eradication of Narcotics Abuse and Illicit Trafficking of Narcotics and Narcotics Precursors: A Siyasah Dusturiyah Perspective - Miftah Nurrahmat; Jujun Jamaludin (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
Bandung City is one of the regions with the highest rate of narcotics abuse vulnerability in West Java, marked by a continuously rising trend of cases. The Bandung City Government responded to this condition through Regional Regulation Number 5 of 2021 concerning P4GNPN, particularly Article 15, which governs prevention efforts through socialization, community empowerment, and cross-sector coordination. This study analyzes the implementation of Article 15 using George C. Edward III's policy implementation theory, measures its effectiveness through Soerjono Soekanto's legal effectiveness theory, and examines its conformity with the principle of siyasah dusturiyah, employing an empirical juridical approach based on interviews and observations of Kesbangpol, the Regional Legal Bureau, community leaders, religious scholars, and academics. The findings show that implementation has proceeded with a fairly positive public response, although its effectiveness remains constrained by limited budget, weak inter-agency (OPD) coordination, discontinuity of the program, insufficient sanctions, and restricted access to data. From the perspective of siyasah dusturiyah, this policy holds strong legitimacy as it aligns with the principle of tasharruf al-imam 'ala ar-ra'iyyah manuthun bi al-mashlahah and the objectives of maqashid al-syari'ah, particularly hifz al-nafs and hifz al-'aql.